ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP MELALUI PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS ETNOMATEMATIKA CANDI TIKUS - Sugandi, Eko; Prayogo, Prayogo; Faizah, Hanim (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
Learning mathematics with a daily life orientation creates a real and optimal learning experience for students, especially in the cultural sphere, which also supports students' mathematical communication skills. This research aims to analyze the mathematical communication skills of junior high school students through ethnomathematics-based Realistic Mathematics Learning, especially at Tikus Temple, Mojokerto Regency. This research is descriptive quantitative research with an ethnographic approach. The subjects used were one class of SMP 48 Surabaya students. Quantitative data was obtained based on students' post-test results. The research results showed that the students' mathematical communication ability test data was normally distributed with a significance value based on the Kolomogorov-Smirnov test of 1,116. Twenty students achieved completion of KKM 65. The results of the One-Sample Statistics test show that the average student calculated value is 72,16 with a standard deviation of 14,593 and a standard error of 2,664. The One-Sample Test results also show a sig. (2-tailed) value of 0,012, meaning that the average value of students' mathematical communication test results is more than or not equal to 70. The minimum completion proportion test results show that the value of tcount ttable so that students' average mathematical communication ability is not equal to 65 and more than 70%.